2016
DOI: 10.1016/j.taap.2016.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of drug-induced arrhythmic risk using limit cycle and autocorrelation analysis of human iPSC-cardiomyocyte contractility

Abstract: Cardiac safety assays incorporating label-free detection of human stem-cell derived cardiomyocyte contractility provide human relevance and medium throughput screening to assess compound-induced cardiotoxicity. In an effort to provide quantitative analysis of the large kinetic datasets resulting from these real-time studies, we applied bioinformatic approaches based on nonlinear dynamical system analysis, including limit cycle analysis and autocorrelation function, to systematically assess beat irregularity. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…While this is likely attributed to both technological advances achieved with advanced engineering of hiPSC-CM as well as a plethora of published data using a multitude of drugs in recent years, there remains some concerns relative to the adult phenotype of the cells used in these emerging in vitro models. 5,21,22 It is important to compare and contrast findings derived from responses in this survey to previously conducted SPS survey as this informs whether change has occurred with regard to study design and practice over time during the conduct of SP studies. In a recent survey that investigated the developing CiPA initiative, 16 it was revealed that a majority (59%) of responders reported that their company had abandoned at least one pharmacophore (or potential "toxicophore") based on data obtained from assays characterizing drug-mediated blockade of I Kr .…”
Section: Discussionmentioning
confidence: 99%
“…While this is likely attributed to both technological advances achieved with advanced engineering of hiPSC-CM as well as a plethora of published data using a multitude of drugs in recent years, there remains some concerns relative to the adult phenotype of the cells used in these emerging in vitro models. 5,21,22 It is important to compare and contrast findings derived from responses in this survey to previously conducted SPS survey as this informs whether change has occurred with regard to study design and practice over time during the conduct of SP studies. In a recent survey that investigated the developing CiPA initiative, 16 it was revealed that a majority (59%) of responders reported that their company had abandoned at least one pharmacophore (or potential "toxicophore") based on data obtained from assays characterizing drug-mediated blockade of I Kr .…”
Section: Discussionmentioning
confidence: 99%